Pengaruh Independensi dan Kompetensi Auditor Internal Terhadap Kualitas Audit Internal: (Survei pada Satuan Pengawasan Internal Perguruan Tinggi Keagamaan di Indonesia) - Bakri Bakri; Mahfiza Mahfiza (Al-Buhuts, 2020)
This study aims to determine the effect of the independence and competence of internal auditors on the quality of internal audit. The method used is quantitative descriptive with a survey approach. The results of the study indicate that auditor independence has a direct (positive) and significant influence on the quality of internal audit, one of the reasons for the lack of quality of internal audit in conducting audits related to the system and application of accounting in the Internal Audit Unit (SPI), because it is still not high/adequate auditor independence. which is indicated by the still not high Programming Independence, Investigate Independence and Reporting Independence of the Inspectorate auditors. To improve the quality of internal audit at the Internal Audit Unit (SPI) in religious universities in Indonesia, it can be done through increasing auditor independence. Independence requires the role and commitment of the leadership (top management) both from the head of internal audit (head of the Internal Audit Unit) more than the top leadership/ Chancellor. In more detail, in order to improve the quality of internal audit through increasing auditor independence. Based on data analysis, the competence of internal auditors affects the quality of internal audit where these results support the theory that the competence of internal auditors affects the quality of internal audit. Due to the lack of high/adequate competence of the auditor as the organizer of the internal audit related to the accounting system and application, the quality of the auditor is questioned in conducting audits where based on the answers to the questionnaire as a whole, it is known that the internal audit is not of high quality. To improve the quality of the internal audit in the Internal Audit Unit (SPI), it can be done through increasing the competence of auditors with adequate education and training to improve the knowledge and skills of auditors.